REPRESENTASI OF DA’WAH MESSAGES THROUGH PAINTINGS; ANALYSIS OF DA’WAH ISLAMIC DA’WAH IN SUFISTIK PAINTINGS @_ ZUKKK WITH A SEMIOTIC APPROACH - romadlany, zakiyah; Ahmad Kavin Billah (Program Studi Komunikasi dan Penyiaran Islam Fakultas Dakwah Universitas Islam Internasional Darullughah Wadda'wah Bangil Pasuruan, 2024)
Painting is an art form of beauty has become increasingly crucial to convey Islamic messages and values in the new digital, da’wah media in the digital era, indicating in broadcasting Islam with various forms of methods, one of which is through painting (sign). This digital da’wah is a trend in society, especially the younger generation, the tendency to learn religion through social media. This research investigates the role of paintings in Islamic preaching. taking a case study of paintings on artists on the Instagram account